2008
DOI: 10.1001/archpsyc.65.5.508
|View full text |Cite
|
Sign up to set email alerts
|

Depression Is Associated With Decreased 25-Hydroxyvitamin D and Increased Parathyroid Hormone Levels in Older Adults

Abstract: The results of this large population-based study show an association of depression status and severity with decreased serum 25(OH)D levels and increased serum PTH levels in older individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
255
8
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(285 citation statements)
references
References 32 publications
14
255
8
8
Order By: Relevance
“…In the Longitudinal Aging Study Amsterdam (Hoogendijk et al, 2008), lower serum 25-hydroxyvitamin D concentrations were observed among elderly subjects with depressive symptoms than those without. In another study of Chinese populations, depressive symptoms were not associated with serum 25-hydroxyvitamin D concentrations (Pan et al, 2009).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the Longitudinal Aging Study Amsterdam (Hoogendijk et al, 2008), lower serum 25-hydroxyvitamin D concentrations were observed among elderly subjects with depressive symptoms than those without. In another study of Chinese populations, depressive symptoms were not associated with serum 25-hydroxyvitamin D concentrations (Pan et al, 2009).…”
Section: Discussionmentioning
confidence: 95%
“…The vitamin D receptor and the vitamin D-activating enzyme 1-a-hydroxylase are widely distributed in the human brain (Berk et al, 2007). Despite such suggestive evidence for a role of vitamin D in depression, few population-based studies have explored depressive symptoms in relation to vitamin D status (Hoogendijk et al, 2008;Pan et al, 2009). We therefore investigated the association between serum 25-hydroxyvitamin D and depressive symptoms in Japanese employees.…”
Section: Introductionmentioning
confidence: 99%
“…PTH stimulates the increased biosynthesis of 1,25-dihydroxyvitamin D when the levels of 25(OH)D are low (38) . PTH may also contribute to depression through a possible mechanism in which low vitamin D level causes an increase in PTH level and hyperparathyroidism is often accompanied by depressive disorders (39) . Our results demonstrated that low vitamin D status was associated with higher levels of depression after adjusting for confounding variables in Malaysian women.…”
Section: Discussionmentioning
confidence: 99%
“…Since it has recently been reported that the vitamin D receptor is distributed in the brain and 25 (OH)-vitamim D activation and the use of vitamin D in cells occur in brain organs, studies on the effects of vitamin D on mental health have been conducted [4]. In addition, vitamin D also affects the synthesis of neurotransmitters such as acetylcholine esterase, serotonin, nerve growth factor, and thyroid hormone, and it has been suggested that vitamin D may thereby affect cognitive function and depression [5].…”
Section: The Need For Researchmentioning
confidence: 99%